(untitled) (Third Sector Social Economic Review, 2026)
The article titled ‘How will I break AI? Post-Luddism in the AI age: Fuzzy MCDM Synergy’ (Darıcı et al., 2024), the concept of Post-Luddism, known in the public sphere as the “fear of unemployment due to artificial intelligence” and studied analytically and empirically for the first time in the literature, requires a holistic and critical framework to understand the complex technological and social problems brought about by the age of artificial intelligence. Moving beyond merely defining Post-Luddism conceptually and providing a more detailed structure and background constitutes the fundamental motivation for this study. In its most general form, Post-Luddism can be defined as a modern critical school of thought that has emerged in response to the rapid development of technology. Building on the historical Luddite movement, this current reinterprets critiques of technology in a human-centred manner within the context of the socio-economic, environmental, and ethical problems of the modern era. Questioning the social impacts of advanced technologies such as artificial intelligence, automation, and digital surveillance, Post-Luddism deeply analyses the transformative effects of technology on individuals and society. In this context, the article aims to present the fundamental characteristics and concerns of Post-Luddism within a comprehensive theoretical perspective, clarifying its place in the age of artificial intelligence.